The European Union's carbon border adjustment mechanism and its effects on Philippine exports - Manguera, Mark Carmelo R.; Abrenica, Ma. Joy V. (Quezon City School of Economics, University of the Philippines Diliman, 2024)
The European Union's (EU) carbon border adjustment mechanism (CBAM) is set to take effect in 2026, with its transition period having begun in October 2023. Its initial implementation will cover the sectors: fertilizers, iron and steel, cement, aluminum, electricity, and chemicals; with a long-term goal of expanding the coverage to all activities under its emissions trading system. While its objective is environmental in nature- addressing carbon leakage- its effects on trade cannot be undermined. This paper adds to existing assessments of the EU CBAM's consequences on developing countries by performing a sectoral analysis based on the specific products identified under EU Regulation 2023/956. Further, the study focuses on the Philippines relative to its regional neighbors, Indonesia and Malaysia. The results are arrived at using the structural gravity model to estimate the elasticity of EU sectoral imports to bilateral tariffs and representing the EU CBAM as carbon tariffs based on the equation by Larch and Wanner (2017). The findings reveal that the implementation of the EU CBAM based on the exporting country's emission intensity will reduce Philippine exports in the iron and steel and cement sectors by as much as 7.63 and 11.61 percent. The repercussions of the EU CBAM are more pronounced for these sectors due to their higher elasticities of substitution and for the Philippines due to its higher emission intensity of production.
Thesis (Master in Development Economics)
Keywords: Exports -- Philippines; Foreign trade -- Philippines